2019
DOI: 10.3390/app9102110
|View full text |Cite
|
Sign up to set email alerts
|

A Survey on Deep Learning-Driven Remote Sensing Image Scene Understanding: Scene Classification, Scene Retrieval and Scene-Guided Object Detection

Abstract: As a fundamental and important task in remote sensing, remote sensing image scene understanding (RSISU) has attracted tremendous research interest in recent years. RSISU includes the following sub-tasks: remote sensing image scene classification, remote sensing image scene retrieval, and scene-driven remote sensing image object detection. Although these sub-tasks have different goals, they share some communal hints. Hence, this paper tries to discuss them as a whole. Similar to other domains (e.g., speech reco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
52
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 124 publications
(60 citation statements)
references
References 97 publications
(121 reference statements)
0
52
0
Order By: Relevance
“…Audebert et al, 2016Audebert et al, , 2017Audebert et al, , 2018Längkvist et al, 2016;Li et al, 2015;Li and Shao, 2014;Volpi and Tuia, 2017;Liu et al, 2018Liu et al, , 2017aPan et al, 2018a,b;Marmanis et al, 2016Marmanis et al, , 2018Wen et al, 2017;Zhao et al, 2017b). A comprehensive review of deep learning applications in the field of remote sensing can be found in ; Ma et al (2019); Gu et al (2019).…”
Section: Related Workmentioning
confidence: 99%
“…Audebert et al, 2016Audebert et al, , 2017Audebert et al, , 2018Längkvist et al, 2016;Li et al, 2015;Li and Shao, 2014;Volpi and Tuia, 2017;Liu et al, 2018Liu et al, , 2017aPan et al, 2018a,b;Marmanis et al, 2016Marmanis et al, , 2018Wen et al, 2017;Zhao et al, 2017b). A comprehensive review of deep learning applications in the field of remote sensing can be found in ; Ma et al (2019); Gu et al (2019).…”
Section: Related Workmentioning
confidence: 99%
“…In the past several years, due to a large amount of training images and high-performance GPUs, deep learning techniques-in particular, supervised approaches such as deep convolutional neural networks (DCNNs)-have achieved relentless success in various high-level computer vision tasks, such as image classification, object detection, semantic segmentation, etc. [2][3][4]. The key advantage of these deep learning techniques is to learn high-level feature representations in an end-to-end fashion, which are more discriminative than traditional ones.…”
Section: Introductionmentioning
confidence: 99%
“…The deep development of remote sensing technology in recent years has induced urgent demands for processing, analyzing and understanding the high-resolution remote sensing images. The most fundamental and key task for remote sensing image analysis (RSIA) is to recognize, detect, classify and retrieve the images belonging to multiple remote sensing categories like agricultural, airplane, forest and so on [1][2][3][4][5]. Among all these tasks, remote sensing image retrieval (RSIR) [2,[6][7][8] is the most challengeable in analyzing remote sensing data effectively.…”
Section: Introductionmentioning
confidence: 99%